Intravascular Large B-Cell Lymphoma Diagnosed on Prostate Biopsy: A Case Report - Nazan Özsan; Banu Sarsık; Asu Fergün Yılmaz; Adnan Şimşir; Ayhan Dönmez (Turkish Journal of Hematology, 2014)
Intravascular large B-cell lymphoma (IVLBCL) is a very rare type of non-Hodgkin lymphoma, usually affecting elderly patients and characterized by selective infiltration of neoplastic cells within blood vessels' lumina. IVLBCL diagnosed with prostatic involvement is extremely rare. We report a patient of 65 years old, having mostly neurological complaints but diagnosed with IVLBCL upon histopathological examination of transurethral prostate resection material, which revealed large neoplastic cell infiltration totally limited within the lumens of small vessels. By immunohistochemistry, neoplastic cell infiltration was positive with MUM1, bcl-6, and bcl-2 and negative with ALK1, CD10, and CD30, with a high Ki-67 proliferation index. CD34 and CD31 staining showed expression in endothelial cells, highlighting the intravascular nature of neoplastic infiltrate. The patient unfortunately refused to receive treatment and died of the disease 8 months after the diagnosis. IVLBCL, though very rare, should be considered in differential diagnosis of all organ biopsies with intravascular infiltration. Further improvements in the understanding of the pathogenesis and biology of this rare type of lymphoma are mandatory.